Assessment of the social attitude of primary school students - Ari Setiawan; Siti Partini Suardiman (REID (Research and Evaluation in Education), 2018)
The implementation of Curriculum 2013 at primary school level brings about its own problems to teachers. A serious problem emerges in the assessment, especially the assessment of core competence for the social attitude aspect. This problem arises because social attitude has many dimensions and requires judgments in diverse forms. In addition, the assessment of social attitude is focused on the affective sphere. The objective of this research is to assess the social attitude of grade IV and/or V students of primary school using three integrated instrument models: self-assessment (SA), peer assessment (PA), and observational assessment (OA). This research employed qualitative approach. The respondents were 58 students chosen by using cluster random sampling and purposive sampling techniques. The data were collected through direct disclosure questionnaire and observation, and analyzed descriptive quantitatively. The results of the research are as follows: (1) the component of honesty attitude is in category A (entrusted); (2) the component of discipline is in category A (entrusted); (3) the responsibility component is in category B (developing); (4) the politeness component is in category B (developing); (5) caring component is in category B (developing); (6) confidence component is category A (entrusted); and (7) students' social attitude is mainly in category B (good) which indicates that most students have good social attitude.